ASSESSING THE ENGLISH AS A FOREIGN LANGUAGE (EFL) UNIVERSITY STUDENTS’ CRITICAL THINKING - Andania, Ruqoyyah Amilia (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2021)
Abstract: Assessment in critical thinking (CT) is essential to be implemented particularly in the English Language Teaching (ELT) classrooms; it can help teachers recognize their students’ English proficiency as well as CT skill level since both of them are interconnected. However, this assessment of CT is not well achieved in most language schools in Indonesia including at the university level since CT is not an independent subject, it is only linked to the main subjects existing in Indonesian curriculum. Therefore, this current study tries to investigate (1) teachers’ perspective on assessing their students’ CT (2) strategies that the teachers use to assess their students’ CT, and how those strategies are implemented. In depth interviews were conducted with two lectures of the English education Department. The findings show that (RQ1) the teachers realize that it is very important to assess students’ CT during teaching-learning process mainly in ELT context even tough CT is not aimed as the main objectives of the course, (RQ 2) teachers use questions and answers, instructions and directions, group discussion and pair assessment strategies to assess their students’ CT through giving questions and instructions to gain their students’ ideas which are implemented in the beginning, main, and closing activities relating to the topic discussed. In addition, they also conduct group discussion to help students actively involved in sharing their ideas, peer assessment is also utilised. In this case, teachers use their own creativity to assess their students’ CT. They relate the assessments given to assess students’ CT based on the goal and objectives of the course, and what should be achieved in that course. From this study, language teachers are suggested to encourage university students by creating classroom activities that lead to developing students' critical thinking based on the goal or objectives of the course, and what should be achieved in that course. In addition, further research is expected to expand this scope by involving more participants in a variety of contexts and fields to achieve more insightful knowledge and experience.    Keywords—Critical Thinking, Assessment, Assessment of Critical Thinking Abstrak: Penilaian berpikir kritis sangat penting untuk diterapkan khususnya di kelas pembelajaran Bahasa Inggris, hal tersebut diklaim dapat membantu guru mengenali kemampuan Bahasa Inggris siswa dan keterampilan berfikir kritis karena keduanya saling berhubungan. Namun, penilaian berfikir kritis ini tidak tercapai dengan baik di sebagian besar sekolah bahasa di Indonesia termasuk di tingkat universitas karena keterampilan berfikir kritis bukanlah mata kuliah yang berdiri sendiri, melainkan terkait dengan mata kuliah utama yang ada dalam kurikulum di Indonesia. Penelitian ini mencoba untuk menyelidiki (1) perspektif dosen dalam menilai kemampuan berfikir kritis mahasiswanya (2) strategi yang digunakan dosen untuk menilai kemampuan berfikir kritis mahasiswa, dan bagaimana strategi tersebut diterapkan. Wawancara secara mendalam dilakukan dengan dua orang dosen dari jurusan Pendidikan Bahasa Inggris di Indonesia. Temuan menunjukkan bahwa (RQ1) para dosen menyadari betapa pentingnya untuk menilai kemampuan berfikir kritis mahasiswa selama proses belajar-mengajar terutama dalam konteks pembelajaran Bahasa Inggris, (RQ 2) dosen menggunakan  strategi pertanyaan dan jawaban, instruksi dan arahan, diskusi kelompok dan penilaian berpasangan untuk menilai kemampuan berfikir kritis mahasiswa mereka. Melalui pemberian pertanyaan dan instruksi untuk mendapatkan gagasan mahasiswa yang diimplementasikan dalam kegiatan awal, utama, dan penutup berkaitan dengan topik yang dibahas. Selain itu, dosen juga menerapkan diskusi kelompok untuk membantu mahasiswa terlibat aktif dalam berbagi ide atau gagasan, dan penilaian rekan juga digunakan. Dalam hal ini, dosen menciptakan ide kreatif mereka sendiri untuk menilai kemampuan berfikir kritis mahasiswanya. Mereka menghubungkan penilaian yang diberikan untuk menilai kemampuan berfikir kritis mahasiswa berdasarkan tujuan pembelajaran, dan apa yang harus dicapai dalam mata kuliah tersebut. Dari penelitian ini, para pengajar Bahasa Inggris disarankan untuk menciptakan kegiatan kelas yang mengarah pada pengembangan kemampuan berfikir kritis mahasiswa berdasarkan pada tujuan pembelajaran, dan apa yang harus dicapai pada mata kuliah tersebut. Selain itu, para peneliti dimasa mendatang diharapkan dapat memperluas cakupan ini dengan melibatkan lebih banyak peserta dalam berbagai konteks dan bidang untuk mencapai pengetahuan dan pengalaman yang lebih mendalam.   Kata Kunci: Berpikir Kritis, Penilaian, Penilaian Berpikir Kritis